Interface Design Usability Testing of Virtual Reality (VR)-Based Learning Environment - D'oria, I.R.; Chen, Chwen Jen; Teh, Chee Siong (2009)
Designing usable and effective interactive virtual reality (VR) systems is a new challenge for human factors specialists. One of the challenges in human factors research is to increase performance efficiency in virtual world. This paper provides results on the usability testing on the interface of VR-based learning environment whereby interface design of a system also do influenced user’s performance in the VR environment. To collect the usability data in this VR environment, we will use Software Usability Measurement Inventory (SUMI) questionnaires for the interface design testing. Suggestions derived from this study are fully address to improve the complex interface design on VR-based learning environment.